Error Analysis of Machining Accuracy of Free-form Surfaces Using On-line Inspection Method - Yueping Chen; Jian Gao; Hao Wen; Detao Zheng; Xin Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper error sources existing in the on-line inspection system for numerical control machines are analyzed. A mathematical model of the geometric errors of a three-axis machining center is created and the pretravel variations are obtained in different directions. Then an error compensation is applied to improve the accuracy of the on-line inspection system. A methodology of spatial statistical analysis of machining errors for free-form surfaces is proposed. Through the on-line inspection of a machined workpiece, the measured points and their machining errors are obtained. By analysis of these machining errors using the spatial statistical analysis, the machining errors are decomposed into systematic errors and random errors, which will provide the basis for machining error compensation during the subsequent process. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1969